FORMULATION AND IN-VITRO EVALUATION OF EFFERVESCENT TABLETS - Dr. Shashikant D. Barhate; Dr. Sandip R. Pawar (Journal of Population Therapeutics and Clinical Pharmacology, 2021)
Hypertension is the commonest cause of high blood pressure in the elderly. The incidence increases with age advancement. Long acting dihydropyridines like amlodipine is very effective antihypertensive agent in management of ISH in elderly because of its vasodilatory as well as negative ionotropic effect. The main Aim of Present work is to Formulate and Evaluate Amlodipine besylate Effervescent and direct compression tablets tablets in order to enhance its Bio-availability by using Amlodipine besylate are the main ingredients in effervescent Tablets and Fast Disintegrating agents like sodium starch glycolate, Crosscarmilose. Different batches of (F1-F6) immediate release tablets of Amlodipine besylate were prepared by using various concentrations of Citric acid & Sodium bicarbonate as effervescent agents and sodium starch glycolate, Cross cormilose as super disintegrates. Evaluation parameters like thickness, hardness, friability, weight variation and disintegration tests of the formulations were found to be satisfactory. Among all prepared formulations F6 was shown desired release pattern than others. Formulations F1- F6 did not show the optimum drug release .Hence effervescent technique is superior to direct compression by super disintegrates. And thus the F6 formulation was found to be the desired immediate release tablet for the treatment of Hypertension